How a hierarchical governance structure influences cultural heritage destination sustainability: A context of red tourism in China. (March 2022) - Wang, Hongyu; Zhang, Beile; Qiu, Hanqin
Abstract: A growing recognition has been observed regarding destination governance in tourism sustainability. Given the hierarchical structure still takes an essential role in destination governance, how this governance structure impacts the sustainability of heritage tourism destinations remains unclear. This research focuses on red tourism destinations in China to analyse how a hierarchical governance structure may incur destination sustainability issues. Using a qualitative case study, the results summarized two streams of conflicts in destination management process: vertical conflicts between central and local governance levels, and horizontal conflicts at local governance level between different stakeholders. Results show that both vertical and horizontal conflicts influence the cultural heritage sustainability in terms of preservation and enhancement, and the conflicts originate from the attributes of hierarchical governance structure. The research supplements the current knowledge of how the hierarchical governance structure influences the sustainability of heritage destinations and provides practical implications to Chinese red tourism destinations.